The Influence of COVID-19 on Antimicrobial-Resistance in Gram-Positive Bacteria at a Private Saudi Hospital: A Five-Year Evaluation - Meshari Alabdullatif (Journal of Pure and Applied Microbiology)
Due to the emergence of antimicrobial-resistance (AR) as a public health threat, the Saudi National Action Plan (SNAP) was implemented in 2017, incorporating various strategies to combat AR. To evaluate the effectiveness of SNAP and the impact of COVID-19, the study analyzed pre- and post-pandemic rates of AR, methicillin-resistant Staphylococcus aureus (MRSA), and multidrug resistance (MDR) among Gram-positive bacteria at a private medical center in Saudi Arabia. This study reviewed the cases of all patients who had been diagnosed with Gram-positive bacterial infection between January 2017 and December 2021. Bacterial strain identification was conducted using VITEK-2 ID-GP cards, while AR, MRSA, and MDR were defined using AST-GP 67 and AST-ST02 cards, all adhering to the manufacturer’s recommended protocols. The five-year study from 2017 to 2021 yielded 6,271 Gram-positive bacteria isolates from patients in a Saudi private hospital. Though the rate of AR initially declined between 2017 and 2019, it spiked significantly from 2020 to 2021. Similarly, the MRSA rate exhibited a substantial decrease (p < 0.05) from 2017 to 2019, followed by a significant rise (p < 0.05) between 2020 and 2021. Out of the isolated pathogens, 1,031 (16.44%) exhibited MDR, with all isolates showing a marked increase (p < 0.05) in MDR from 2020 to 2021. The study highlights the aggravating impact of the COVID-19 pandemic on AR, underscoring the need for the SNAP to intensify its efforts in combating AR.